Single‐cell transcriptomic landscape of cardiac neural crest cell derivatives during development. (27th September 2021) - Chen, Wen; Liu, Xuanyu; Li, Wenke; Shen, Huayan; Zeng, Ziyi; Yin, Kunlun; Priest, James R; Zhou, Zhou
Abstract: The migratory cardiac neural crest cells (CNCCs) contribute greatly to cardiovascular development. A thorough understanding of the cell lineages, developmental chronology, and transcriptomic states of CNCC derivatives during normal development is essential for deciphering the pathogenesis of CNCC‐associated congenital anomalies. Here, we perform single‐cell transcriptomic sequencing of 34, 131 CNCC‐derived cells in mouse hearts covering eight developmental stages between E10.5 and P7. We report the presence of CNCC‐derived mural cells that comprise pericytes and microvascular smooth muscle cells (mVSMCs). Furthermore, we identify the transition from the CNCC‐derived pericytes to mVSMCs and the key regulators over the transition. In addition, our data support that many CNCC derivatives had already committed or differentiated to a specific lineage when migrating into the heart. We explore the spatial distribution of some critical CNCC‐derived subpopulations with single‐molecule fluorescence in situ hybridization. Finally, we computationally reconstruct the differentiation path and regulatory dynamics of CNCC derivatives. Our study provides novel insights into the cell lineages, developmental chronology, and regulatory dynamics of CNCC derivatives during development. Synopsis: Using single‐cell transcriptomics this study presents the heterogeneity and differentiation trajectory of cardiac neural crest cell (CNCC) derivatives after migrating into the heart, identifying that many CNCC‐derivatives had already committed or differentiated to a specific lineage when migrating into the heart. A single‐cell transcriptomic atlas of CNCC derivatives during mouse embryonic and neonatal development. CNCC‐derived mural cells are present in the heart. Many CNCC‐derivatives had already committed or differentiated to a specific lineage when migrating into the heart. Abstract : A single‐cell transcriptomic atlas of mouse cardiac neural crest cell (CNCC) derivatives reveals that many had already committed or differentiated to a specific lineage when migrating into the heart.